2002
DOI: 10.1677/joe.0.1750813
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, safety and tolerability of three dosage regimens of buccal adhesive testosterone tablets in healthy men suppressed with leuprorelin

Abstract: We used a randomised, double-blind, crossover design to evaluate the pharmacokinetics, safety and tolerability of three doses of buccal adhesive testosterone tablets (BATT). Twenty-four healthy men, whose endogenous testosterone was suppressed to c5·38 nmol/l with leuprorelin acetate, took BATT (10, 20 or 30 mg) daily for 10 days. There was a 4-day washout between treatments. Substantial testosterone absorption occurred from BATT, and mean serum testosterone, free testosterone and dihydrotestosterone (DHT) con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 26 publications
(12 reference statements)
2
5
0
Order By: Relevance
“…The interassay CVs were of 8.8% and 7.9% at FT concentrations of 0.018 nmol/L and 0.85 nmol/L, while the intraassay CVs were of 7.4% and 7.1% at the same FT concentrations, respectively. Referring to the normal values used by Baisley et al, [40] FT levels in normal SHBG phenotype and variant SHBG phenotype in this study [ Table 3] were within the range in normal values. FT levels between normal SHBG phenotype when compared with variant SHBG phenotype did not differ (p = 0.778).…”
Section: Discussionsupporting
confidence: 73%
“…The interassay CVs were of 8.8% and 7.9% at FT concentrations of 0.018 nmol/L and 0.85 nmol/L, while the intraassay CVs were of 7.4% and 7.1% at the same FT concentrations, respectively. Referring to the normal values used by Baisley et al, [40] FT levels in normal SHBG phenotype and variant SHBG phenotype in this study [ Table 3] were within the range in normal values. FT levels between normal SHBG phenotype when compared with variant SHBG phenotype did not differ (p = 0.778).…”
Section: Discussionsupporting
confidence: 73%
“…With regard to concentrations of androgen and growth factors, the bioluminescent approach demonstrated in this communication could provide critical information on the concentration as well as the half-life of DHT in tissues. Assuming the intensity of luciferase imaging corresponds directly with the tissue level of DHT, using the non-invasive imaging approach we were able to calculate the half-life of tissue DHT in vivo to be 20 h by photon emission units, a result that has not been reported hitherto and which is consistent with the pharmacokinetic data of serum DHT (Wang et al 1998, Baisley et al 2002.…”
Section: Molecular Imaging Of Mouse Prostate · C-l Hsieh and Others 299supporting
confidence: 72%
“…27 According to the guidelines used by Baisley et al, the average levels of FT in this study 0.063 ± 0.0013 nmol/L is included in the range of normal values. 28 The other result of my study in normal SHBG phenotype showed that FT levels 0.065±0.01 nmol/L, while in variant SHBG phenotype 0.064±0.77 nmol/L. 21 The results of this study…”
Section: Resultsmentioning
confidence: 50%